Physical fitness performance of young professional soccer players does not change during several training seasons in a Spanish elite reserve team: club study, 1996-2013 - Los Arcos, A.; Martins, J. (The Journal of Strength and Conditioning Research, 2018)
The purpose of this study was to assess the changes in physical fitness performance in young professional soccer players during several training seasons in a Spanish elite reserve team. Physical test values (i.e., vertical jump test, straight line sprint test, and discontinuous and progressive submaximal running test) of 97 young professional soccer players who belonged for at least 2 consecutive seasons to the reserve team of a Spanish professional team from 1996 to 2013 were analyzed. A distinction was made between the soccer players who were promoted to the Spanish first/second divisions (n = 38) and those who were not (n = 59) (until the end of the 2016/2017 season). Players were also classified according to their playing positions. Independently of the competitive level reached and the playing position, the variability of the fitness performance was limited (coefficient of variation <6%) and the players did not improve their fitness values (effect size = small) from the first to the last season in which they were enrolled in the team (after 2-4 seasons). During the last stage of training in an elite soccer academy, young professional soccer players achieve a very similar physical fitness performance when their soccer competence is evaluated, and other soccer performance factors are those which make them stand out for selection.